A Comparative Analysis of the Intended Mathematics Curriculum of Cambodia and Singapore: Focus on Geometry - Sieng Veasna (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2025)
Cambodian students’ achievement is low in geometry problem-solving ability. This study aims to compare the intended mathematics curriculum of Cambodia and Singapore, with a specific focus on geometry. Four recently revised Cambodian mathematics syllabi, published in 2018 and two Singaporean mathematics syllabi, published in 2020, have been collected and analyzed following the General Topic Trace Mapping procedure. This analysis reveals significant differences between Cambodian and Singaporean mathematics curricula in design, structure and coherence, followed by domain, sub-domain, contents, sub-contents and learning outcomes within and across the grade. It also highlighted that the Cambodian mathematics curriculum on geometry lacks coherence in content, sub-content, and learning outcomes, potentially lowering student achievement. Enhancing curriculum coherence could significantly improve student learning outcomes in Cambodia.